Net Based Examination: Small Group Tutoring, Home Assignments, and Large Group Automatic and Peer Assessment - Karlsson, Göran (International Journal of Emerging Technologies in Learning (iJET), 2007)
This paper deals with net based examination, tutoring and scaffolding of groups of different sizes: First for very small groups, then for normal sized groups around 100 students and finally for very large groups. The three different methods can be applied to internationally based courses. Methods which support deep learning through tutoring, scaffolding, project work and peer learning are also mentioned.